Twisted Frobenius Identities from Vertex Operator Superalgebras - Alexander Zuevsky (Advances in Mathematical Physics)
In consideration of the continuous orbifold partition function and a generating function for all n-point correlation functions for the rank two free fermion vertex operator superalgebra on the self-sewing torus, we introduce the twisted version of Frobenius identity.